2014
DOI: 10.1103/physrevd.89.124034
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the post-Newtonian circular restricted three-body problem with compact objects

Abstract: By applying scaling transformations to distance and time, we obtain the first post-Newtonian equations of motion for a relativistic circular restricted three-body problem, where the Newtonian terms do not depend on the separation of a parent binary, though the post-Newtonian terms do. The postNewtonian contributions consist of the relativistic effects from the circular orbital frequencies between the primaries and those from the primaries to a third body. When the former post-Newtonian contribution and the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…(4.15), which depend on a parameter ρ, possess for ρ ¼ 0 a periodic solution whose characteristic exponents (see Appendix B) are all nonvanishing, they have again a periodic solution for small values of ρ. In our case, the small parameter ρ is the Planck length l P , and when ρ ¼ 0 we revert to the three-body problem in post-Newtonian mechanics, for which, in the circular restricted case, one knows from recent work [13] that orbits may be unstable, or bounded chaotic, or bounded regular. In the case of Newtonian mechanics instead, Chenciner and Montgomery [14] have found a class of solutions where three bodies of equal mass move periodically on the plane along the same curve.…”
Section: Hamiltonian Equations Of Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…(4.15), which depend on a parameter ρ, possess for ρ ¼ 0 a periodic solution whose characteristic exponents (see Appendix B) are all nonvanishing, they have again a periodic solution for small values of ρ. In our case, the small parameter ρ is the Planck length l P , and when ρ ¼ 0 we revert to the three-body problem in post-Newtonian mechanics, for which, in the circular restricted case, one knows from recent work [13] that orbits may be unstable, or bounded chaotic, or bounded regular. In the case of Newtonian mechanics instead, Chenciner and Montgomery [14] have found a class of solutions where three bodies of equal mass move periodically on the plane along the same curve.…”
Section: Hamiltonian Equations Of Motionmentioning
confidence: 99%
“…The desired periodic solutions, whose existence is a special rather than generic property [1,2,13], can be written in the form…”
Section: ð6:18þmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of research papers (e.g., [23]; [12]; [14]) are available on the 1 st order post-Newtonian equations of motion for the restricted problem of three bodies which are deduced by using the Einstein-Infeld-Hoffmann theory (e.g., [19], [18]). [17] studied the dynamics of the planar circular restricted problem of three-bodies in the context of a pseudo-Newtonian approximation by using the Fodor-Hoenselaers-Perjé procedure, while [20] examined the influence of the separation between the primaries. It is concluded that the post-Newtonian dynamics substantially differ from the corresponding classical Newtonian dynamics provided the distance between the primaries is sufficiently small.…”
Section: Introductionmentioning
confidence: 99%
“…When the value of the transition parameter ∈ (0, 0.67752839], the libration points L 11,12,13,14 , L 15,16,17,18 and L 19,20,21,22 move away from the centers of the primaries P 1 , P 2 , and P 3 , respectively, while on the other hand the libration points L 2,7,8 move towards the centers of the primaries P 1 , P 2 , and P 3 , respectively. In particular, L 1,3,5,6,9 and L 10 , move towards the central libration point L 4 .…”
mentioning
confidence: 99%